1994
DOI: 10.1007/bf02244780
|View full text |Cite
|
Sign up to set email alerts
|

Controlled comparison of nefazodone and amitriptyline in major depressive inpatients

Abstract: Nefazodone, a phenylpiperazine antidepressant, exhibits novel dual activity on serotonin (5-HT) neurons; it binds to 5-HT2 receptors and inhibits 5-HT reuptake. Flexible doses of nefazodone (100-400 mg/day) and amitriptyline (50-200 mg/day) were compared in 106 major depressive inpatients in a 6-week double-blind study. Results showed significant superiority of amitriptyline over nefazodone on all rating instruments: Montgomery and Asberg depression rating scale (P < 0.0001), Hamilton depression scale (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 21 publications
1
5
0
2
Order By: Relevance
“…Several studies comparing NEF with imipramine found equal efficacy [9][10][11][12]; the same holds true for another study versus AMI [13].…”
Section: Introductionmentioning
confidence: 41%
“…Several studies comparing NEF with imipramine found equal efficacy [9][10][11][12]; the same holds true for another study versus AMI [13].…”
Section: Introductionmentioning
confidence: 41%
“…Analysis of the comparative efficacy of SSRIs and tricyclic antidepressants in in-patients (judged likely to be a more severely affected group) provided a slightly larger estimate of effect favouring tricyclic antidepressants, though again non-significant. The overall estimate of effect in this grouping of studies 8,16,27,35,44,47,67,69,73,74,77,80,81,82,86,88,91,94,98,99,105,108,111,118,120,127 (using a random effects model) was 0.10 (95% CI -0.072 to 0.272, Q = 49.1, d.f. = 22, P = 0.008).…”
Section: Efficacy Of Antidepressantssupporting
confidence: 41%
“…10 Supporting the assumption that antidepressants do not act merely by means of a placebo effect, depressed patients were treated with drugs, including central stimulants, barbiturates, opiates and antipsychotics, but without satisfactory effect, 30 even before the serendipitous discovery of the first antidepressants, imipramine and iproniazide; 31 had drug treatment of depression been merely a matter of a psychological placebo response, these compounds should have appeared just as effective as imipramine or iproniazide. Moreover, a large number of trials have revealed significant differences between two antidepressants (or putative antidepressants) in trials including no placebo arm; [32][33][34][35][36] had the superiority of antidepressants over placebo in controlled trials been merely the result of the patient realizing that he/she has not been given active treatment, such an outcome would be difficult to explain given that the participants in these trials knew that they were not at risk of receiving placebo. The present data, suggesting that antidepressants do not act merely by means of a placebo effect, are well in line with these observations.…”
Section: Discussionmentioning
confidence: 41%